Rancang Bangun Aplikasi Penawaran dan Pencarian Kerja Paruh Waktu (Part Time) Berbasis Lokasi - Alfian Eko Susilo Putro; Herman Tolle; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The rapid increase in smartphone usage, especially with the android platform and the need for information on part-time job vacancies are becoming a trend in some circles such as students. From those two things that drive writers to create a job search application that can provide quick and accurate access to part-time job-seekers, by building this app using android smartphone job seekers will be simplified in viewing the details of the job just by going through Smartphone and also sign up for the job just by sending a CV through one Touch on his smartphone screen. Research begins with the assessment of previous research so that will facilitate the author in developing this application. After the assessment phase is executed the author makes some UML diagrams that are use case diagrams, sequence diagrams and activity diagrams. From the results of the application design the authors perform blackbox testing using the use case testing method, this method to test the application based on the use case that has been made. Test results from blackbox only give the test results from the user side functionally. From the design and development that has been done, it is concluded that the application can be made by using use case, activity diagram, database, sequence diagram, and interface. To show the job location using geolocation. Geolocation taken using latitude and longitude.